LncRNA—UCA1 enhances cell proliferation and 5-fluorouracil resistance in colorectal cancer by inhibiting miR-204-5p - Bian, Zehua; Jin, Liugen; Zhang, Jiwei; Yin, Yuan; Quan, Chao; Hu, Yaling; Feng, Yuyang; Liu, Heyong; Fei, Bojian; Mao, Yong; Zhou, Leyuan; Qi, Xiaowei; et al. (Scientific reports, 2016)
Recent preliminary studies reported the in vitro tumor-promoting effects of long non-coding RNA urothelial carcinoma associated 1 (UCA1) in colorectal cancer (CRC). However, the in vivo functions and molecular mechanism of UCA1 in CRC remain unclear. Therefore, we investigated the detailed role and mechanism of UCA1 in CRC. We found that UCA1 was up-regulated in CRCs and negatively correlated with survival time in two CRC cohorts. Functional assays revealed the in vitro and in vivo growth-promoting function of UCA1 and revealed that UCA1 can decrease the sensitivity of CRC cells to 5-FU by attenuating apoptosis. Further mechanistic studies revealed that UCA1 could sponge endogenous miR-204-5p and inhibit its activity. We also identified CREB1 as a new target of miR-204-5p. The protein levels of CREB1 were significantly up-regulated in CRCs, negatively associated with survival time and positively correlated with the UCA1 expression. The present work provides the first evidence of a UCA1-miR-204-5p- CREB1 / BCL2 / RAB22A regulatory network in CRC and reveals that UCA1 and CREB1 are potential new oncogenes and prognostic factors for CRC.